Six new Chinese species of the Pachyprotasis melanosoma group （Hymenoptera: Tenthredinidae) with a key to the species - Zhong, Yihai; Li, Zejian; Wei, Meicai (Zootaxa, 2015)
The Pachyprotasis melanosoma group is defined as a part of the former P. rapae group, and a key to this species of this group from China is provided. Six new species from China are described in this paper: P. coximaculata Zhong & Wei, sp. n.; P. coxipunctata Zhong & Wei, sp. n.; P. hengshani Zhong & Wei, sp. n.; P. maculoscutellata Zhong & Wei, sp. n.; P. pailongensis Zhong & Wei, sp. n. and P. qilianica Zhong & Wei, sp. n.